2021
DOI: 10.3988/jcn.2021.17.2.176
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review of Psychiatric Comorbidities in Adults with Epilepsy

Abstract: Background and Purpose Mental illness is disproportionately common in people with epilepsy (PWE). This systematic literature review identified original research articles that reported the prevalence of psychiatric comorbidities based upon clinical assessments in a sample of PWE and assessed the clinical features of the populations found in studies included in our review of mental health comorbidity. Methods The included articles were written in English and published fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 45 publications
2
45
0
3
Order By: Relevance
“…In addition, about 50% of our patients presented a certain stress level. Psychiatric disorders are frequent comorbidities in MTLE, manifesting in about 75% of these patients, compared to lower rated reported in extratemporal and generalized epilepsies [30] . More than half of MTLE patients suffer from depression, and about 40% of them from anxiety, including post-traumatic stress disorder and generalized anxiety disorder.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, about 50% of our patients presented a certain stress level. Psychiatric disorders are frequent comorbidities in MTLE, manifesting in about 75% of these patients, compared to lower rated reported in extratemporal and generalized epilepsies [30] . More than half of MTLE patients suffer from depression, and about 40% of them from anxiety, including post-traumatic stress disorder and generalized anxiety disorder.…”
Section: Discussionmentioning
confidence: 86%
“…Psychiatric disorders are disproportionally more common in PWE, with mood and anxiety disorders being the most prevalent. A recent meta-analysis of 23 articles among PWE performed between 2008 and 2018 found a prevalence of 24.2% for depressive disorder and 11.1% for anxiety disorder [27] . Our results indicate a slightly lower percentage for depression.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review revealed that mood and anxiety disorders (35.0% and 25.6%, respectively) are the most common psychiatric comorbidity while disorders belonging to psychotic spectrum like schizophrenia (1.7%) or bipolar disorders (6.2%) are rare. [ 8 ] Hallucinations, illusions, and sensory illusions and distortions, cognitive illusions, time distortion, thought and speech disturbance and motor automatisms have all been reported as ictal phenomena. [ 9 ] Fugue state, also known as a twilight state can be defined as an altered state of consciousness with varying grades of motor activity and amnesia for the event.…”
Section: Discussionmentioning
confidence: 99%